Sustaining reductions in catheter related bloodstream infections in Michigan intensive care units: observational study. (4th February 2010) - Pronovost, Peter J; Goeschel, Christine A; Colantuoni, Elizabeth; Watson, Sam; Lubomski, Lisa H; Berenholtz, Sean M; Thompson, David A; Sinopoli, David J; Cosgrove, Sara; Sexton, J Bryan; Marsteller, Jill A; Hyzy, Robert C; et al.
Abstract : Objectives To evaluate the extent to which intensive care units participating in the initial Keystone ICU project sustained reductions in rates of catheter related bloodstream infections. Design Collaborative cohort study to implement and evaluate interventions to improve patients' safety. Setting Intensive care units predominantly in Michigan, USA. Intervention Conceptual model aimed at improving clinicians' use of five evidence based recommendations to reduce rates of catheter related bloodstream infections rates, with measurement and feedback of infection rates. During the sustainability period, intensive care unit teams were instructed to integrate this intervention into staff orientation, collect monthly data from hospital infection control staff, and report infection rates to appropriate stakeholders. Main outcome measures Quarterly rate of catheter related bloodstream infections per 1000 catheter days during the sustainability period (19-36 months after implementation of the intervention). Results Ninety (87%) of the original 103 intensive care units participated, reporting 1532 intensive care unit months of data and 300 310 catheter days during the sustainability period. The mean and median rates of catheter related bloodstream infection decreased from 7.7 and 2.7 (interquartile range 0.6-4.8) at baseline to 1.3 and 0 (0-2.4) at 16-18 months and to 1.1 and 0 (0.0-1.2) at 34-36 months post-implementation. Multilevel regression analysis showed that incidence rate ratios decreased from 0.68 (95% confidence interval 0.53 to 0.88) at 0-3 months to 0.38 (0.26 to 0.56) at 16-18 months and 0.34 (0.24-0.48) at 34-36 months post-implementation. During the sustainability period, the mean bloodstream infection rate did not significantly change from the initial 18 month post-implementation period (−1%, 95% confidence interval −9% to 7%). Conclusions The reduced rates of catheter related bloodstream infection achieved in the initial 18 month post-implementation period were sustained for an additional 18 months as participating intensive care units integrated the intervention into practice. Broad use of this intervention with achievement of similar results could substantially reduce the morbidity and costs associated with catheter related bloodstream infections.